2016
DOI: 10.1177/0309524x16645482
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane risk assessment for offshore wind plants

Abstract: This study describes a framework for estimation of structural damage to offshore wind plants during hurricanes. Related risk assessment is fundamentally dependent on the estimation of hurricane-generated wind speed exceedance probabilities at selected hub heights of wind turbines in the plant and on estimation of associated wind turbine loads. As part of a framework for risk assessment introduced here, synthetic storm tracks are first simulated over the ocean using available historical tropical storm data; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Lian et al investigated the wind load characteristics of OWTs under typhoon conditions with full 360‐degree wind directions considering the variations in the wind direction and different wind rotor parking positions using a 3‐D numerical simulation. Kim and Manuel carried out a framework for estimation of structural damage to offshore wind plants during hurricanes. Wei et al simulated a 5 MW turbine supported by a jacket structure, where a set of 1000 synthetic hurricane events were used to represent hurricane conditions, and the impact of wind and wave directions and structural orientation were quantified through a series of nonlinear static analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Lian et al investigated the wind load characteristics of OWTs under typhoon conditions with full 360‐degree wind directions considering the variations in the wind direction and different wind rotor parking positions using a 3‐D numerical simulation. Kim and Manuel carried out a framework for estimation of structural damage to offshore wind plants during hurricanes. Wei et al simulated a 5 MW turbine supported by a jacket structure, where a set of 1000 synthetic hurricane events were used to represent hurricane conditions, and the impact of wind and wave directions and structural orientation were quantified through a series of nonlinear static analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Rose et al (2013) simulated the wind field of wind farms off the US coast using the Coupled Hurricane Intensity Prediction System developed by Emanuel et al (2004) and quantified the risk from hurricanes to offshore wind farms through damage to the functionality of wind turbines. They highlighted that 10% of offshore wind turbines could be shut down simultaneously owing to hurricane damage and that 6% of offshore wind turbines might be destroyed within 10 years Kim and Manuel (2016) developed a model of tropical cyclone intensity evolution and simulated the wind field of wind farms. They performed hazard assessment for wind turbines by analyzing the load distribution and the wind speed exceedance probability distribution for individual turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Since industrial-scale offshore wind energy development along the US East Coast began to be discussed seriously, a series of studies have sought to quantify the degree of risk posed to offshore wind farms by hurricanes. These studies have included attempts to identify appropriate structural performance levels and nonlinear structural analysis methods for offshore wind structures (Wei et al, 2014(Wei et al, , 2016, multihazard risk analyses (Hallowell et al, 2018;Kim and Manuel, 2016;Mardfekri and Gardoni, 2015;Valamanesh et al, 2015Valamanesh et al, , 2016, and analysis of wind-structure interaction (Amirinia and Jung, 2017). On the whole, these studies have shown that hurricane winds can indeed pose important risks to offshore wind turbines but that such risk can be mitigated by appropriate design approaches.…”
Section: Introductionmentioning
confidence: 99%